Natural Convection Heat Transfer of Liquid Metal Gallium Nanofluids in a Rectangular Enclosure. Issue 1 (17th September 2015) - Qi, Cong; Cui, Xin; Liu, Yibo; Yang, Zhongbo; Huang, Chao
Abstract : A new mixed nanofluid (Cu/diamond–gallium [Cu/diamond–Ga] nanofluid) is proposed, and the mass ratio of Cu nanoparticles and diamond nanoparticles in the new mixed nanofluid is 10:1. The natural convection heat transfer of Cu/diamond–Ga nanofluid, Cu–gallium (Cu–Ga) nanofluid, and liquid metal gallium with different volume fractions in a rectangular enclosure is investigated by a single‐phase model in this paper. The effects of temperature difference, nanoparticle volume fraction and the kinds of nanofluid on the natural convection heat transfer are discussed. The natural convection heat transfer of the three kinds of fluids is compared. It is found that Nusselt numbers of the Cu/diamond–Ga nanofluid along with X direction increases with the nanoparticle volume fraction and temperature difference. Cu/diamond–Ga nanofluid can enhance the heat transfer by 73.0% and 9.7% at low‐temperature difference (Δ T = 1 K) compared with liquid metal gallium and Cu–Ga nanofluid, respectively. It also can enhance the heat transfer by 85.9% and 5.2% at high‐temperature difference (Δ T = 11 K) compared with liquid metal gallium and Cu–Ga nanofluid, respectively.